A history of the Circle of Concerned African Women Theologians, 1989-2007 - Fiedler, Rachel Nyagondwe (Mzuni Press, 2017)
When "African Theology" was first formulated, women played just a small role. In 1989 Mercy Amba Oduyoye set out to change this by creating the Circle of Concerned African Theologians in order to them a voice. The Circle of Concerned African Women Theologians is an African Baby, born in an ecumenical surrounding. Though there were other movements addressing the issue of gender inequalities in church and society, circle theologies are distinct from other women's liberation movements in that they are theologies formed in the context of African culture and religion. This book traces the Circle history from 1989 to 2007.